Improving the Management of Patients with Acute Coronary Syndrome Complicated by Arrhythmias at the Stages of Treatment - Muxiddinovna, Babaeva Maxsuda (Central Asian Journal of Medical and Natural Science, 2023)
According to literature data, cardiac arrhythmia and conduction disorders are a constant complication of acute coronary (ACS) and on the first day of the disease they are observed in 90-95% of patients (Alavi B.A., Yakubov M.M., 2008). The recorded late potentials of the ventricles of the heart are highly sensitive markers of the development of ventricular tachycardia, being the most common causes of death in patients with ACS (Karetnikova, V.N. 2010). The relevance of this problem lies in the low efficiency of diagnosing the onset of rhythm disorders, predicting their course and insufficiently effective treatment. Pathological changes in the myocardium are accompanied by various disorders of the electrical activity of the heart, but they are all characterized by general patterns and prognostically unfavorable in terms of the occurrence of fatally dangerous rhythm disturbances (Osinchuk Ya.B., 2012). The occurrence of myocardial ischemia due to a decrease in coronary blood flow leads to a violation of biochemical processes in mitochondrial cells, as a result, the contractile function of cardiomyocytes decreases (Kochkina M.S. 2015).